PENERAPAN METODE FRAME BY FRAME DALAM PEMBUATAN ANIMASI TATA CARA HAJI SESUAI SUNNAH RASUL MENGGUNAKAN APLIKASI 3DS MAX - Aldina Syahfaridzah; Khairunnisa; Dharmawati (METHOMIKA: Jurnal Manajemen Informatika & Komputerisasi Akuntansi, 2021)
Advances in technology in the field of information are developing very rapidly at this time, especially information in the field of animation. The animation is a visual form that moves and is used to present information and learning that is difficult to understand if delivered in general. The use of animation media is specially made to find out the procedures for the Hajj pilgrimage in order to increase knowledge for someone who wants to perform the Hajj or want to know the Hajj procedures because Hajj is the fifth pillar of Islam where if someone carries it out, much wisdom will be gained. Information about the pilgrimage procedures is packaged with 3D animation and created using 3Ds Max application and the frame by frame method, where all movements of the animation are arranged using frames. So that the resulting learning media, namely animated videos that add insight and information for someone because it is packaged with media that is more attractive and easy to understand, namely animation.